Prenatal Temperature Shocks Reduce Cooperation: Evidence from Public Goods Games in Uganda - Duchoslav, Jan (Frontiers in Behavioral Neuroscience, 2017)
Climate change has not only led to a sustained rise in mean global temperature over the past decades, but also increased the frequency of extreme weather events. This paper explores the effect of temperature shocks in utero on later-life taste for cooperation. Using historical climate data combined with data on child and adult behavior in public goods games, I show that abnormally high ambient temperatures during gestation are associated with decreased individual contributions to the public good in a statistically and economically significant way. A 1 standard deviation rise in mean ambient temperature during gestation is associated with a 10% point decrease in children's cooperation rate in a dichotomous public goods game, and the reduced taste for cooperation lasts into adulthood.